(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
In this article we expose the Euclidean theory of vision and, in particular, those theorems that deal with prospective representation. Our aim is to show how the central perspective was known in the Hellenistic era both from a theoretical and practical point of view as evidenced by the analysis of some imperial period frescoes found in Rome. In the second part of this article we look at the Euclidean perspective theorems, using the Cartesian coordinates and the limit idea.